Reinventing geotechnical engineering laboratory classes - Jaksa, M.; Airey, D.; Kodikara, J.; Shahin, Mohamed; Yuen, S. (CRC Press, 2012)
In his 1987 Nash Lecture, Prof. John Burland questioned the educational value of requiring undergraduate students to undertake routine laboratory testing, such as the triaxial, direct shear and oedometer tests. He stated that students are far from inspired by these. Other highly respected geotechnical engineering educators and researchers have expressed similar reservations about the current nature of geotechnical engineering laboratory classes. This paper re-examines the nature, structure and assessment of geotechnical laboratory experiments, explores their educational aims and proposes a framework whereby these classes can be more effective places of learning, be more engaging and more efficient. This last aspect is particularly challenging in recent times, as class sizes continue to grow to the point where educators are questioning the sustainability of resource-hungry and time-intensive laboratory classes.